Ratio of blood and marrow-derived cells in bone marrow transplantation. Issue 5 (May 1982) - Kay, H; Lumley, H; Clink, H M; Powles, R L
Abstract : The content of the cell suspensions used in bone marrow transplantation can vary by at least twelvefold in the ratio of bone marrow-derived to blood-derived cells. The ratio is somewhat higher in young donors but is similar for male and female donors and is not closely correlated with the incidence of graft v host reactions.